Bronchospasme induit par l`exercice chez des sportifs de compétition en milieu tropical humide - Ouattara, S.; Balayssac-Siransy, A. E.; Konaté, A.; Tuo, N.; Keita, M.; Dah, C.; Bogui, P. (Science & Sports, 2012)
Objectives: To assess the prevalence of exercise-induced bronchospasm in athletes living in humid tropical environment. Methods: This prospective investigation, carried out in Abidjan in september 2001, have concerned 108 athletes of competition. After a questionnaire relative to asthma and atopie, each athlete underwent an exercise challenge. The temperature and the humidity were recorded. Criteria for exercise-induced bronchospasm was a decrease of the forced expiratory volume in one second greater or equal to 10% and/or a decrease of the peak expiratory flow greater or equal to 15%. Results: The averages of ambient temperature and relative humidity were respectively 30.1 ± 1.6 °C et 82.6 ± 6.3%. According to the questionnaire, 13% of athletes were asthmatics or had symptoms of asthma and 36.1% had symptoms of atopie. According to the fall of the forced expiratory volume in 1 second, the fall of the peak expiratory flow and the fall of forced expiratory volume in 1 second and/or peak expiratory flow, the prevalences of exercise-induced bronchospasm were respectively 22.2%, 35.2% and 42.6%. These falls occured especially between the 1st and the 15th minute after exercise. Conclusion: The results of this study were not in favour of the hypothesis according to which inhalation of warm and wet air protected from bronchospasm.